Introduction to the Special Issue The Political Economy of Agrarian Change: Essays in Appreciation of Henry Bernstein. (July 2016) - Campling, Liam; Lerche, Jens
Abstract : This special issue presents five essays and an interview in appreciation of Henry Bernstein. The essays – by major scholars in the field of agrarian political economy – engage with different aspects of Bernstein's oeuvre: from direct critical reflections on his approach to the peasantry and the agrarian question through to arguments developed in connection to his work on commercial capitalism, landed property and the relationship between petty production and accumulation. This introduction briefly sets out some of the major aspects of Bernstein's distinctive editorial, pedagogical and theoretical contributions. It suggests that his most crucial and lasting contribution is in his absorption and ability to apply Marx's theory and method as a living theoretical and analytical approach to the study of agrarian political economy.